Photocatalytic treatment of coffee shop wastewater using zinc oxide (ZnO) catalyst - Marhaini, Marhaini; Fernianti, Dewi; Khodijah, Siti (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the effectiveness of the photocatalytic process using Zinc Oxide (ZnO) as a catalyst in reducing caffeine concentration and improving water quality parameters, including Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD), Total Suspended Solids (TSS), and pH. The investigated variables include the initial pH levels (4, 7, and 9) and ZnO catalyst concentrations (1000, 2000, and 3000 ppm), both with and without the addition of 0.01 M H2O2. The photocatalytic process was conducted under UVA illumination for 4 hours. Results indicated that the optimal condition was at pH 7 with a ZnO concentration of 3000 ppm, achieving a caffeine degradation efficiency of 74.58%. The COD value significantly decreased from 5203 mg/L to 4470 mg/L, while BOD slightly decreased from 948 mg/L to 917 mg/L. The lowest TSS value was recorded at pH 7 with 98 mg/L, indicating good ZnO stability under neutral conditions. The addition of H2O2 tended to reduce the final pH and enhance degradation performance at pH 9, but reduced caffeine degradation efficiency at pH 7 due to adsorption competition between H2O2 and caffeine on the catalyst surface. The photocatalytic method using ZnO effectively reduced caffeine levels and major pollutant parameters in coffee shop wastewater, demonstrating its potential as an environmentally friendly alternative for wastewater treatment technology.